The effect of earning management, managerial ownership and firm size in the return of acquisition companies in Indonesia Stock Exchange 2011-2017 period - Andini, Ni Luh; Sukartha, I Made (International research journal of management, IT and social sciences, 2020)
This research was conducted to see the effect of earnings management, managerial ownership, and firm size, and net profit margin (NPM) as a control variable on stock returns. The research location is on the Indonesia Stock Exchange (BEI) in 2018 by accessing the official website of the Indonesia Stock Exchange, www.idx.co.id, and using the Indonesian Capital Market Directory which provides complete company financial statement information and explanations and other information. The population used in this study were companies that acquired other companies in the period 2011 to 2017 and were listed on the Indonesia Stock Exchange (IDX) totaling 75. The total sample that was ultimately used in this study was 30 acquiring companies selected by the purposive sampling method. The analytical method used in this study is the multiple linear regression analysis. The results of this study found that based on the results of research on the effect of earnings management, managerial ownership, and firm size on acquirer stock returns in 2011-2017, of the four research variables one of them is net profit margin (NPM) as a control variable affecting stock returns.